PERKAWINAN POLIGAMI DI INDONESIA - Syaiful Muda’i; Rizki Azna Finurika (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
Polygamous marriage has been a controversial issue throughout history between the pros and cons. For those who support the existence of polygamous marriages, they read QS. al-Nisa' verse 3 with an emphasis on the permissibility of a man to marry up to 2,3,4 women. As for those who are against polygamy, they read QS. al-Nisa' verse 3 by focusing on the potential for injustice caused by polygamy so that the monogamy system should be upheld. Polygamy in Indonesia as an emergency way in a marriage, is regulated in law. Several reasons are needed to allow polygamy to occur, as well as the technical rules that accompany it. This shows that polygamy cannot just be done without looking at the underlying reasons.